Performance Optimization of a Turbocharged Spark-Ignition VVA Engine at Part Load - Bozza Fabio; Teodosio Luigi (Journal of Advances in Applied & Computational Mathematics, 2015)
Nowadays, modern internal combustion engines show more and more complex architectures in order to improve their performance. Referring to the spark-ignition (SI) engines, downsizing philosophy and Variable Valve Actuation (VVA) systems allow to reduce the Brake Specific Fuel Consumption (BSFC) at low and medium load, while maintaining the required performance at high load. On the other hand, the above solutions introduce additional degrees of freedom for the engine control, requiring longer calibration time and experimental effort. In the present work, a twin-cylinder turbocharged VVA SI engine is numerically investigated by a one-dimensional (1D) model (GT-PowerTM). The considered engine is equipped with a fully flexible VVA actuation system, realizing an Early Intake Valve Closure (EIVC) strategy. Proper "user routines" are implemented in the code to simulate turbulence and combustion processes. In a first stage, 1D engine model is validated against the experimental data under part load condition, both in terms of overall performance and combustion evolution. The validated 1D engine model is then integrated in a multipurpose commercial optimizer (mode FRONTIERTM) with the aim to identify the engine calibrations that simultaneously minimize BSFC and Brake Mean Effective Pressure (BMEP) under part load operation at a specified engine speed of 3000rpm. In particular, the decision parameters of the optimization process are the EIVC angle, the throttle valve opening and the waste-gate valve opening and combustion phasing. Proper constraints are assigned for the pressure in the intake plenum in order to limit the gas-dynamic noise radiated by the intake mouth. The adopted optimization approach shows the capability to reproduce with a very good accuracy the experimentally advised optimal calibration, corresponding to the numerically derived Pareto frontier in the Brake Mean Effective Pressure (BMEP)-BSFC tradeoff. The optimization also underlines the advantages of an engine calibration based on a combination of EIVC strategy and intake throttling, rather than a purely throttle-based calibration. The developed automatic procedure allows for a "virtual" calibration of the considered engine on completely theoretical basis and proves to be very helpful in reducing the experimental costs and the engine time-to-market.